Lexical structure among poets in the Abbasid era (Damascus University Journal of arts and humanities sciences, 2025)
This research reveals the lexical structure of the poets of the Abbasid era. In it, the researcher looks at the linguistic fabric used in women’s poetry in the Abbasid era, traces the meanings of the word and its connotations within the text, and reveals its relationships with other words that all combine to achieve the intended meaning, in addition to demonstrating the ability and skill of the Abbasid poet in investing in her linguistic reserve to form meaning, by choosing words appropriate to their connotations from her linguistic dictionary. Adding new connotations and their impact on the distinction of women’s poetry, and bringing women’s discourse in the Abbasid era to thehorizon of creativity. The study showed the importance of the lexical structure among the poets of the Abbasid era, the linguistic level that characterized women’s poems in that era, how linguistic vocabulary was used, the extent of the contribution of the women poets’ own language, and their distinct style in achieving significance and revealing the secrets of the poetic text among the poets of the Abbasid era.
Keywords: : lexical structure; poets; the Abbasid era